Management of Humeral and Glenoid Bone Loss in Recurrent Glenohumeral Instability - Mascarenhas, Randy (Hindawi Publishing Corporation, 2014)
Recurrent shoulder instability and resultant glenoid and humeral head bone loss are not infrequently encountered in the population today, specifically in young, athletic patients. This review on the management of bone loss in recurrent glenohumeral instability discusses the relevant shoulder anatomy that provides stability to the shoulder joint, relevant history and physical examination findings pertinent to recurrent shoulder instability, and the proper radiological imaging choices in its workup. Operative treatments that can be used to treat both glenoid and humeral head bone loss are outlined. These include coracoid transfer procedures and allograft/autograft reconstruction at the glenoid, as well as humeral head disimpaction/humeroplasty, remplissage, humeral osseous allograft reconstruction, rotational osteotomy, partial humeral head arthroplasty, and hemiarthroplasty on the humeral side. Clinical outcomes studies reporting general results of these techniques are highlighted.